ANALOGY AS A BASIC TECHNIQUE IN THE PROCESS OF CREATING NEW PRODUCTS (Innovation in Woodworking Industry and Engineering design, 2026)
The analogy as a basic technique used in a number of design methods as a result of the application of close and distant similarities from other areas, has been studied in the present report. It is based on a very common and recommended technique of creative thinking. Analogy is the basic means of the subjective logic of people, based on the systematic approach to the comparison of objects. Making analogies develops intuition and imagination, as in fact it is a result of the qualitative synthesis of the appearance of the technical system by a distant similarity. The professional development of designers is connected with the gradual acquisition and development of the capacity of synectic techniques. The analogies are very widely used in the design of industrial products. The creation of new products and services can be significantly enhanced by applying this technique, compared with the use of random ideas. The aim of this report is to show the effectiveness of this technique for improving the creative process and present the working mechanisms of the most frequently used design methods using the technique of analogy.